OBSERVATIONS ON SOME ASPECTS OF BIOLOGY OF THE BLACK CROAKER ATROBUCCA NIBE (JORDAN AND THOMPSON) FROM KAKINADA - Murty, V Sriramachandra (Indian Journal of Fisheries, 2011)
Observatioins on some aspects of biology of Atrobucca nibe are made from Kakinada. The length-weight relationship is described by the equation log W = -5.524308 + 3.213476 log L. The fluctuations in relative condition factor appear to be associated with fluctuations in gonad cycle. Individuals release ova in two batches during the spawning season which extends from Feibuary to July in the area. The length at fiirst maturity is estimated at 145 mm. The s-sx rstio indicates predominance of males in most months and length groups.